Impacts des changements climatiques sur les relations plantes-herbivores dans l'Arctique - Doiron, Madeleine (Université Laval, 2014)
When species at different trophic levels respond to climate change at different rates, this may lead to a trophic mismatch between the phenology of consumers and that of their resources. As polar regions are warming more rapidly than the rest of the planet, migratory birds breeding in the Arctic are expected to be among the species most affected by trophic mismatch in the wake of rapid climate change. This study examines the impact of climate warming on the interactions between an arctic herbivore, the greater snow goose (Chen caerulescens atlantica), and its food plants on Bylot Island, Nunavut, Canada. Using small greenhouses, we examined the impact of increased temperatures on plant biomass and a proxy of nutritive quality, nitrogen concentration, of graminoid plants used by geese during the brood-rearing period. This experiment showed that annual warming significantly increased biomass of graminoids but also led to an acceleration of the seasonal decline in plant nutritive quality and resulted in a decrease in the nitrogen concentration of plants by up to 14% during the period of gosling growth. We also showed that satellite-derived Normalized Difference Vegetation Index (NDVI) can be used as a proxy to determine date of peak nitrogen concentration in some tundra plants, and can thus be a reliable measure of the early changes in the timing of the availability of high quality food for herbivores. Using NDVI, we were then able to estimate the date of peak nitrogen in years when we had no empirical data on plant phenology. Finally, we analysed long-term data on climate, plant phenology and the reproduction of geese in order to examine the potential impact of mismatched reproduction on the growth of young. We found that geese are only partially able to adjust their breeding phenology to compensate for annual changes in the timing of high quality food plants, and that gosling body mass and structural size at fledging was reduced when trophic mismatch was high. Our results support the hypothesis that trophic ...